Longer cutting intervals on the characteristics of Guinea grass: morphogenetic, productive, and nutritional traits - Junges, Luciana; Gomes, Eva Nara Oliveira; Candido, Anderson Ramires; Ítavo, Luís Carlos Vinhas; Ítavo, Camila Celeste Brandão Ferreira; Coelho, Elson Martins; Difante, Gelson dos Santos; Santos, Geraldo Tadeu dos; Dias, Alexandre Menezes (Acta Scientiarum. Animal Sciences, 2023)
The aim of this study was to examine the effect of longer cutting intervals on morphogenetic and structural traits, herbage production, nutritional value, and in vitro digestibility of Guinea grass cv. Mombaça (Mombaça grass). Four cutting intervals (49, 63, 77, and 91 days) were evaluated in two crop years (2015-2016 and 2016-2017) during the rainy season, in two replicates. Cutting intervals influenced structural and morphogenetic traits, except for number of live leaves (4.35 leaves tiller-1) and final leaf length (72.94 cm) in the 2015-2016 crop year. As the cutting intervals increased, dry matter yield and stem percentage increased, whereas leaf percentage and leaf-to-stem ratio declined. Regardless of the evaluated crop year, the dry matter, acid detergent fiber, and lignin contents increased linearly; however, the neutral detergent fiber content was unaffected. Cutting intervals affected the crude protein content and in vitro digestibility. Considering leaf appearance rate, stem appearance rate, and leaf-to-stem ratio, the recommended harvest age for Mombaça grass for optimum yield and nutritional value is 77 days.